Base-Controlled Completely Selective Linear or Branched Rh(I)-Catalyzed C–H ortho-Alkylation of Azines without Preactivation - Tran, Gaël (Angew Chem Int Ed Engl, 2017)
A [Rh(I)]/bisphosphine/base catalytic system for the ortho-selective C–H alkylation of azines by acrylates and acrylamides is reported. This catalytic system features an unprecedented complete linear or branched selectivity that is solely dependent on the catalytic base that is used. Complete branched selectivity is even achieved for ethyl methacrylate, which enables the introduction of a quaternary carbon center. Excellent functional group compatibility is demonstrated for both linear and branched alkylations. The operational simplicity and broad scope of this transformation allow for rapid access to functionalized azines of direct pharmaceutical and agrochemical relevance.